Pemberdayaan Masyarakat Berbasis Green Entrepreneurship - Rani Nur Fitrianti; Runik Puji Rahayu; Junaidi Efendi; Rachman Hakim; Nur Syakherul Habibi; Muslimatul Aina; Rohmaniyah; Nurul Alfian; Ustman (CV. Multi Kreasi Media, 2023)
Public concern for environmental preservation is increasingly worrying. The community's insensitivity by carrying out illegal logging, illegal harvesting of natural products, and continuous littering of waste triggers floods, landslides, and climate change. The importance of preserving nature is the duty and responsibility of all of us. Due to natural disasters, they can disrupt community activities which then have an impact on the surrounding economy. Green Entrepreneurship is a series of activities to solve environmental or social problems through innovative creative ideas that have a positive impact on the environment and social life of the community. This counseling and training is aimed at opening the training participants' insight into green entrepreneurship and its contribution to improving the economy of the community, namely the community in Ceguk village. This outreach and training on green entrepreneurship produces community groups that play an important role in contributing to creating a friendly environment and creating waste banks to reduce the accumulation of waste in rivers.